Etnobotani Kayu Khombow (Ficus spp.) di Kampung Asei, Distrik Sentani Timur, Jayapura - Asiman M. Manik; Henderina J. Keiluhu; Suriani Br. Surbakti; Sara Yuliana (Jurnal Biologi Papua, 2022)
The use of Khombow bark (Ficus spp.) for traditional handicrafts is a form of forest product utilization by the Sentani community in East Sentani District, Jayapura. The purpose of this study was to identify the types of Khombow wood used by the Sentani Tribe in Kampung Asei Jayapura and to reveal the ethnobotanical aspects of the Khombow tree. Ethnobotanical data were collected by interviewing of Khombow bark collectors and craftsmen from the village, while observations on the species of Khombow wood by identifying specimens collected in the forest around Kampung Asei which were followed by purposive observation of their distribution. The results showed that there are two types of Khombow wood that are often used by residents as raw materials for bark crafts, namely the red Khombow (Ficus nodosa Teijsm & Binn.) and the white Kombow (Ficus variegata Blume). Red kombow wood is easier to find during observation than white Khombow wood, thought to be a result of overharvesting in the previous time and its ease of processing. The traditional use of Khombow wood is preceded by smoothing the fibers and drying before being painted according to traditional motifs, using a variety of dyes from natural and artificial materials that have been widely sold. Over time, the use of Khombow bark by the Sentani community has become increasingly diverse into craft materials such as hats, bags, other decorations, shifting from just traditional clothing materials.Key words: ethnobotany; Ficus spp.; Sentani; wood fiber; traditional crafts.